2012
DOI: 10.1103/physrevb.85.094419
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the inverse Faraday effect via a stimulated Raman scattering process

Abstract: We study theoretically the origin and mechanism of the ultrafast inverse Faraday effect, which is a magnetooptical effect, attracting much interest nowadays. Laser-induced subpicosecond spin dynamics in hydrogenlike systems and isolated many-electron atoms are investigated in order to get insight into this process. We show that the stimulated Raman scattering process leads to a change of the magnetic state of a system. We obtain the time evolution of the induced magnetization, its dependencies on laser propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 32 publications
2
51
0
Order By: Relevance
“…28 In the following, we will disregard the band dispersion, a common approximation in theories of Raman scattering 29 that is allowed for low doping levels and/or large detuning. The electric field component of monochromatic light with frequency ω 0 and wave vector q ẑ is E(t) 30 For a laser pulse width of 40-100 fs with a frequency that is not too close to the resonance, the above criterion is satisfied byh/E g ≈ 0.5 fs for our material.…”
Section: Model Hamiltonian and Second-order Time-dependent Perturmentioning
confidence: 89%
“…28 In the following, we will disregard the band dispersion, a common approximation in theories of Raman scattering 29 that is allowed for low doping levels and/or large detuning. The electric field component of monochromatic light with frequency ω 0 and wave vector q ẑ is E(t) 30 For a laser pulse width of 40-100 fs with a frequency that is not too close to the resonance, the above criterion is satisfied byh/E g ≈ 0.5 fs for our material.…”
Section: Model Hamiltonian and Second-order Time-dependent Perturmentioning
confidence: 89%
“…Coherent magnetization control via Raman scattering [10][11][12][13][14][15][16][17][18][19] , in particular, is attracting attention. Typical examples are the inverse Faraday effect (inverse FE) 10 and the inverse Cotton-Mouton effect (inverse CME) 12 , in which circularly and linearly polarized light pulses, respectively, induce an effective magnetic field in a magnetically ordered medium 3 .…”
mentioning
confidence: 99%
“…However, most AOS samples are amorphous [8,9] and are hard to simulate without significant approximations. To this end, a unified understanding is still missing, but several promising mechanisms have been proposed, which include the inverse Faraday effect [7,10], spin-flip stimulated Raman scattering [11,12], magnetic circular dichroism [13], magnetic sublattice competition [14], pure thermal effect [15,16] and ultrafast exchange scattering [17]. Recently, Lambert et al [18] reported AOS in an ultrathin ferromagnetic [Co(0.4 nm)/Pt(0.7 nm)] 3 multilayer.…”
mentioning
confidence: 99%